PENERAPAN STRATEGI DIGITAL MARKETING, TEORI ANTRIAN TERHADAP TINGKAT KEPUASAN PELANGGAN: (Studi Kasus di MyBCA Ciputra World Surabaya) - Bagas Ilham Lucyantoro; Moch. Rizaldy Rachmansyah (Fakultas Ekonomi Universitas 45 Surabaya, 2017)
Implementation of digital marketing strategy, Queue Theory on customer satisfaction level at myBCA Ciputra World Surabaya. This study aims to find out digital marketing. Queue Theory to the level customer satisfaction in myBCA. The population in this study are customers or customer who transact in the myBCA area. Samples were taken as many as 100 respondents for 1 month in july 2017 with accidental tehnique. With quantitative aproach, primary data collection techques obtain from the responses of respondents. Data analysis tehcniques use are multiple regression analysis, test validity, test reliability, hypothesis testing.